Free-Radical Polymerization of Styrene: Kinetic Study in a Spinning Disc Reactor (SDR) - Vicevic, Marija; Novakovic, Katarina; Boodhoo, Kamelia (Frontiers in Chemical Engineering, 2021)
Free-radical styrene polymerization conducted in a spinning disc reactor (SDR) results in significant increases in conversion in one disc pass, equivalent to a few seconds of residence time, with little change in the number/weight average molecular weights and polydispersity compared to a batch pre-polymer. Results of our experimental studies are presented in this paper and a rationale, based on simulation studies, is offered to explain these observations. It is shown that phenomena such as large increases in conversion that do not impact on molecular weights and molecular weight distribution is a result of a simultaneous increase in both the initiator decomposition rate and the propagation rate. Developed constant variance model was used to estimate reaction parameters at different temperatures and subsequently – activation energy and pre-exponential factor in a SDR. Data analysis at various operating temperatures suggested activation energy for the styrene polymerisation in the SDR as 40.59 ± 1.11 kJ/mol.